The Analysis Study Of Type 2 Diabetes Mellitus As Risk Factor For Cardiovascular Disease: A Comprehensive Systematic Review - Pieters Manaek Tua Bakara (The Indonesian Journal of General Medicine, 2025)
Background: Diabetes mellitus (DM) is prevalent worldwide and linked to rising cardiovascular morbidity and mortality, increasing healthcare burdens. DM complications include atherosclerosis, ischemic heart disease, and peripheral arterial disease, primarily driven by insulin resistance and hyperglycemia, leading to atherosclerosis progression. This systematic review aims to analyze current evidence on the risk factors influencing cardiovascular disease in diabetes mellitus type 2 patients based on literatures of the last 10 years. Methods: The study adhered to PRISMA 2020 standards, examining English literature from 2014 to 2024. It excluded editorials, reviews from the same journal, and submissions without a DOI. PubMed, SagePub, SpringerLink, and Google Scholar were utilized as literature sources. Result: Initially retrieving 360 articles from online databases (PubMed, SagePub, SpringerLink and Google Scholar) eight relevant papers were selected after three rounds of screening for full-text analysis. Conclusion: This study underline the importance of early intervention, dietary and lifestyle changes, and tailored medication in light of the substantial cardiovascular risks associated with Type 2 Diabetes (T2DM). Reducing risks requires a multimodal strategy that is customized to each patient's unique profile.